2020
DOI: 10.1038/s41598-020-64256-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation Profiles of Human Blood, Cell Culture Medium, and Water for Perfusion of 3D-Bioprinted Tissues using the FABRICA Bioreactor Platform

Abstract: Persistent and saturated oxygen distribution from perfusion media (i.e., blood, or cell culture media) to cells within cell-dense, metabolically-active biofabricated tissues is required to keep them viable. Improper or poor oxygen supply to cells within the tissue bulk severely limits the tissue culturing potential of many bioreactors. We added an oxygenator module to our modular FABRICA bioreactor in order to provide stable oxygenation to biofabricated tissues during culture. In this proof of concept study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Research by Chen et al (2020) demonstrated the impact of temperature control on cell growth and function. The study revealed that maintaining the desired temperature within the bioreactor, matching the physiological conditions of the targeted tissue, contributed to cell growth resembling their natural environment [280]. Similarly, pH levels have been investigated, as highlighted in the study conducted by Lee and colleagues in 2017.…”
Section: Bioreactorsmentioning
confidence: 96%
“…Research by Chen et al (2020) demonstrated the impact of temperature control on cell growth and function. The study revealed that maintaining the desired temperature within the bioreactor, matching the physiological conditions of the targeted tissue, contributed to cell growth resembling their natural environment [280]. Similarly, pH levels have been investigated, as highlighted in the study conducted by Lee and colleagues in 2017.…”
Section: Bioreactorsmentioning
confidence: 96%
“…For example, OsteoGen bioreactor systems (Tissue Growth Technologies) can simultaneously apply shear pressures via flow perfusion up to 12 samples. Multiple such perfusion-based systems, commercial or otherwise, have been used for 3D tissue culture to understand the role of growth factors, hormones, inflammatory reactions, antimicrobial therapy, bone ingrowth, and cancer metastasis [15] , [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The benefit in comparison with the commercial MechanoCulture system is that the Endurobone bioreactor will apply mechanical loading directly onto the bone tissue. The biggest advantage of the new design compared to the perfusion systems used in several earlier studies [15] , [16] , [17] , [18] , [19] , [20] , [21] will be the presence of dynamic mechanical loading, which is critically needed for the extended culturing of bone tissue. Hence with the design of EnduroBone bioreactor publicly available through the current work, a wider research community can readily and affordably replicate the bioreactor and thus will make bone-related research more inclusive, affordable, and user-friendly.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The FABRICA bioreactor is a 3D-printed bioreactor that can culture and perfuse 3D-printed tissues in an aseptic environment in real time. 45 Chen et al 74 demonstrated that the FABRICA bioreactor is capable of maintaining physiologic oxygen saturation levels in the water, human blood, and culture media. Given this promising feature, the system may be adapted to provide a means of maintaining perfusion throughout 3D organ printing, although this has been only characterized in the case of 3D bioprinting of genetically engineered pig liver model.…”
Section: Current Obstacles and Recent Progress In 3d Liver Bioprintingmentioning
confidence: 99%
“…Given this promising feature, the system may be adapted to provide a means of maintaining perfusion throughout 3D organ printing, although this has been only characterized in the case of 3D bioprinting of genetically engineered pig liver model. 74 Further optimization of current bioink composition and perfusion kinetics will be necessary to ensure viable 3D bioprinting of hepatic parenchyma.…”
Section: Current Obstacles and Recent Progress In 3d Liver Bioprintingmentioning
confidence: 99%